Anthropogenic Hybridization Contributes to the Naturalization of Introduced Domestic Mallards (Anas platyrhynchos) at the Expense of Native New Zealand Gray Ducks (A. s. superciliosa) - Joshua I. Brown; Jennifer L. Sheppard; Jonathon Mohl; Irene E. Engilis; Andrew Engilis Jr.; Philip Lavretsky (Ecology and Evolution, 2025)
ABSTRACT Anthropogenically mediated hybridization can lead to several outcomes, with the most severe being hybrid swarms and the genetic extirpation of local populations. With the frequency of introductions by humans increasing, understanding the genetic consequences is critical for future conservation actions. Here, we investigate the consequences of domestic Mallard (Anas platyrhynchos) introductions in New Zealand (NZ) on the genetic integrity of native NZ Gray Ducks (Anas superciliosa superciliosa; known locally as Pārera). Although presumed to be genetically extinct, pockets of pure Gray Ducks persist (around 9% of samples), with the western portion of the South Island as the core of their range. In contrast, introduced Mallards have experienced widespread introgression from Gray Ducks that has likely facilitated their rapid establishment and expansion throughout NZ. Moreover, levels of gene flow and divergent selective pressures have resulted in NZ Mallards no longer genetically resembling their original stock and instead have resulted in a hybrid swarm. Estimates of genomic vulnerability for NZ Mallards suggest higher resiliency to future ecological changes as compared to local NZ Gray Ducks. While conservation of NZ's uniquely adapted Gray Duck should remain the priority, we discuss the evolutionary implications of naturalization resulting from anthropogenic hybridization for a now self‐sustaining Mallard population.